A Study on the Impact of Financial Socialization and Financial Management Behavior on Start-up Intention: Mediating Effect of Entrepreneurship - Kang, Gyung-Lan; Park, Cheol-Woo; Jang, Seung-Hwan (International Review of Management and Marketing, 2025)
After COVID-19, youth participation in the financial market became active in our society due to the digital transformation of industrial structure, the emergence of various financial transaction means such as big technology and fintech, and the rise of asset prices. This study examined the effect of financial socialization and financial management behavior of university students in Korea, potential entrepreneurs, on start-up intention and the mediating effect of entrepreneurship. To this end, a survey was conducted on university students in Busan and Gyeongnam, and a total of 207 responses were verified using SPSS 28.0 as a sample. As a result of the study, it was found that financial socialization and financial management behavior had a positive effect on the progressiveness, risk tolerance, and innovativeness of entrepreneurship, and had a positive effect on start-up intention. It was found that the progressiveness, risk tolerance, and innovativeness of entrepreneurship between financial socialization and start-up intention had a positive mediating effect. It was found that the risk tolerance and innovativeness of entrepreneurship between financial management behavior and start-up intention had a positive mediating effect, but it was confirmed that progressiveness had no mediating effect. The results of this study suggest that financial socialization, education on financial management behavior, and fostering entrepreneurship are very important to promote practical start-up for university students who are potential entrepreneurs.